The Past and Future Estimates of Climate and Streamflow Changes in the Western Dvina River Basin - Danilovich, Irina; Zhuravlev, Sergey; Kurochkina, Lubov; Groisman, Pavel (Frontiers in Earth Science, 2019)
The study presents an assessment of the recent and projected changes of the middle and upper Western Dvina River runoff and regional climate during the 20th and 21st centuries. For this assessment, we used historical runoff data, the output of EURO-CORDEX consortium calculations for scenarios RCP4.5 and RCP8.5, and hydrological model “Hydrograph”. Analysis of monthly runoff data for the 1945-2015 period revealed positive trends for each of five months from December to April. These trends are statistically significant at the 0.05 level. No significant trends were found for other months. Significant negative trends were established for spring flood peak discharges (from -69 to -88 m3 s-1 per 10 years). Usually, maximum discharges are observed during spring floods. Minimum discharges during winter low-water period were increased by 6 m3 s-1 per 10 years. The annual runoff trend was statistically significant only at the Polotsk gauging station (9.5 m3/s per 10 years). To the end of the current century over the study region, estimates of projected meteorological parameters (air temperature and precipitation) show positive tendencies of air temperature (from 2.4ºC to 4.7oC depending on scenario) and precipitation (up to 15-30 mm). Changes of seasonal and annual temperature and precipitation vary depending on the models and scenarios used. The strongest changes were noticed for the RCP8.5 scenario. The greatest changes within each scenario were revealed for the winter and spring seasons. It is projected that during the 2021-2100 period according to both RCP scenarios, annual discharges will not change in the upper part of the Western Dvina River Basin and increase by 10-12% in its lower part. The maximum spring flood discharges in both RCP scenarios are expected to decrease by 25 %. The minimum runoff of winter low-flow period is expected to increase by up to 60-90% above the present long-term mean values.